Comparative Life Cycle Assessment of Carbon Fiber and Nano-Silica Modified Asphalt Mixtures - Sabry, Marwa; Abdelsalam , Moustafa; Gamal , Ahmed; Eisa, Mohamed S. (Salehan Institute of Higher Education, 2026)
In recent years, several studies have focused on enhancing the performance of asphalt mixtures using various additives; however, the environmental implications of these modifications have received limited attention. Accordingly, this study aims to evaluate the environmental impacts of asphalt mixtures incorporating carbon fiber (CF) and nano silica (NS) using the Life Cycle Assessment (LCA) methodology. In the current study, four mixtures were modelled and analyzed using SimaPro software: conventional asphalt mix (CAM), carbon fiber asphalt mix (CFAM), nano silica asphalt mix (NSAM), and carbon fiber–nano silica asphalt mix (CFNSAM). The assessment included the production cycle from raw material extraction to wearing surface installation, integrating laboratory performance data with the Ecoinvent v3.6 inventory. Results indicated that CAM exhibited the lowest environmental burden, whereas CFNSAM showed the highest impact resulting from the considerable energy inputs associated with carbon fiber fabrication. NSAM offered a balanced outcome, with moderate environmental impacts and satisfactory mechanical performance, positioning it as a more sustainable alternative. Overall, nano silica modification demonstrates promising potential for eco-efficient pavement applications.